Autonomic innervation in multiple system atrophy and pure autonomic failure. Issue 12 (26th July 2010) - Donadio, V; Cortelli, P; Elam, M; Di Stasi, V; Montagna, P; Holmberg, B; Giannoccaro, M P; Bugiardini, E; Avoni, P; Baruzzi, A; Liguori, R
Abstract : Background: Pure autonomic failure (PAF) and multiple system atrophy (MSA) are both characterised by chronic dysautonomia although presenting different disability and prognosis. Skin autonomic function evaluation by indirect tests has revealed conflicting results in these disorders. Here, the authors report the first direct analysis of skin sympathetic fibres including structure and function in PAF and MSA to ascertain different underlying autonomic lesion sites which may help differentiate between the two conditions. Methods: The authors studied eight patients with probable MSA (mean age 60±5 years) and nine patients fulfilling diagnostic criteria for PAF (64±8 years). They underwent head-up tilt test (HUTT), extensive microneurographic search for muscle and skin sympathetic nerve activities from peroneal nerve and punch skin biopsies from finger, thigh and leg to evaluate cholinergic and adrenergic autonomic dermal annexes innervation graded by a semiquantitative score presenting a high level of reliability. Results: MSA and PAF patients presented a comparable neurogenic orthostatic hypotension during HUTT and high failure rate of microneurographic trials to record sympathetic nerve activity, suggesting a similar extent of chronic dysautonomia. In contrast, they presented different skin autonomic innervation in the immunofluorescence analysis. MSA patients showed a generally preserved skin autonomic innervation with a significantly higher score than PAF patients showing a marked postganglionic sympathetic denervation. In MSA patients with a long disease duration, morphological abnormalities and/or a slightly decreased autonomic score could be found in the leg reflecting a mild postganglionic involvement. Conclusion: Autonomic innervation study of skin annexes is a reliable method which may help differentiate MSA from PAF.